The Effect of Loneliness on Nomophobia In Students at Yaspi Senior High School - Hafni, Merri; Istiana, Istiana; Wulansari, Tiara (Journal of Counseling and Educational Research, 2024)
The purpose of this study was to determine the description of Nomophobia in students who have feelings of loneliness, to determine the description of students who experience loneliness, and to measure how much loneliness affects Nomophobia in students at SMA Yaspi. Based on the Solvin formula with a 5% error rate, the researcher gave a questionnaire to 88 students with a population of 113 students. This study used the UCLA-LS Version 3 measurement scale for the balance variable and the NMP-Q measurement scale for the Nomophobia variable. The research method used was quantitative. The data analysis technique was carried out using Simple Linear Regression Analysis which was calculated with the help of the SPSS (Statistical Program for Social Science) 27 for windows program. The results of the study Loneliness has a positive and significant effect on Nomophobia in students at SMA Yaspi which can be interpreted that the higher the level of equality felt, the more Nomophobia behavior will increase. This is based on the results of the calculations produced that the tcount value> ttable (2.660> 1.663) so that Ha is accepted. And the calculated F value = 7.075 with a significance level of 0.009 <0.05, then the regression model can be used to predict the participation variable or in other words there is an influence of the Loneliness variable on the Nomophobia variable. The implications of the research results can be used as a guidance and counseling service program creation at SMA Yaspi.